2022
DOI: 10.1161/strokeaha.122.038798
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Utility of Computed Tomography Perfusion in the Telestroke Setting

Abstract: Background: Definitive diagnosis of acute ischemic stroke is challenging, particularly in telestroke settings. Although the prognostic utility of CT perfusion (CTP) has been questioned, its diagnostic value remains under-appreciated, especially in cases without an easily visible intracranial occlusion. We assessed the diagnostic accuracy of routine CTP in the acute telestroke setting. Methods: Acute and follow-up data collected prospectively from consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…It is a collaboration between the Prince of Wales Hospital, eHealth NSW, the NSW Agency for Clinical Innovation (ACI), and the NSW Ministry of Health in partnership with the Australian Stroke Foundation. The NSW Telestroke Service was rolled out progressively to its total coverage, with the final sites activated in June 2022, providing services to 23 rural hospitals across NSW [41].…”
Section: Project Conception and Scopingmentioning
confidence: 99%
“…It is a collaboration between the Prince of Wales Hospital, eHealth NSW, the NSW Agency for Clinical Innovation (ACI), and the NSW Ministry of Health in partnership with the Australian Stroke Foundation. The NSW Telestroke Service was rolled out progressively to its total coverage, with the final sites activated in June 2022, providing services to 23 rural hospitals across NSW [41].…”
Section: Project Conception and Scopingmentioning
confidence: 99%
“…It was also noticed in a recent study that including CTP as part of a telestroke imaging protocol was associated with a definitive diagnosis of acute ischemic stroke in approximately one in five cases where NCCT and CTA were nondiagnostic. 28 Our study provides some common reasons that trainees miss stroke-related arterial occlusions (Figure 1). For example, such occlusions were most common in the PCA and M2 territories.…”
Section: Discussionmentioning
confidence: 90%
“…It was also noticed in a recent study that including CTP as part of a telestroke imaging protocol was associated with a definitive diagnosis of acute ischemic stroke in approximately one in five cases where NCCT and CTA were nondiagnostic. 28…”
Section: Discussionmentioning
confidence: 99%
“…The selection of patients with perfusion imaging builds on previous imaging selected tenecteplase trials which demonstrated the improved biological mechanisms of tenecteplase over alteplase and supports the trial where only confirmed ischemic strokes are enrolled to reduce the trial mimic rate seen on other phase III trials 6,7 to support definitive diagnosis. 14 The TASTE study excludes patients with planned endovascular treatment, an important consideration where the treatment effect of endovascular thrombectomy is likely to be larger than thrombolysis. Thrombolysis remains critical in stroke management where endovascular therapy is currently only recommended for patients with an LVO (accounting for 14–20% of all ischemic stroke), especially as bridging thrombolysis pre-endovascular therapy remains standard of care.…”
Section: Discussionmentioning
confidence: 99%